THE MEDIA AS A SUBJECT OF PROPAGANDA OF POLITICAL AND LEGAL CULTURE (Scientific journal of the Fergana State University, 2024)
The purpose of this article is to theoretically substantiate the fact that visits to the media - as a formative subject of political and legal culture - are manifested under the influence of social relations in society, the sphere of human behavior.